Practice, organisation and quality control of digitization projects - Reerink, Henriette (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2003)
In the previous paper Dennis Schouten discussed the different aspects of preservation microfilming in projects carried out within the scope of Metamorfoze, the Dutch national preservation programme for library materials. I will do the same now for digitisation projects, which are executed within the framework of Metamorfoze. I will focus on the planning, workflow and implementation of Metamorfoze digitisation projects, on quality control and organizational aspects, and will relate these facets to preservation.